Adjudicating Conflicting Christologies - Buckley, James J. (Philosophy & theology, 1991)
In this study of Marshall’s Christology in Conflict, the author deals with three questions and issues which can be raised regarding Marshall’s argument: his account of the historical shape of the problem, his critique of Rahner, and his use of Barth’s christology.